ANTIHYPERGLYCAEMIC, ANTIHYPERLIPIDAEMIC AND ANTIOXIDANT ASSAYS(IN VIVO) OF NYMPHAEA PUBESCENS LEAF EXTRACT - KIRAN KUMAR ANGADI; AMMANI KANDRU; ABDUL RAHAMAN (International Journal of Pharma and Bio Sciences, 2013)
The present study was designed to investigate the possible antidiabetic, hypolipidaemic and antioxidant effects of methanol extract of Nymphaea pubescens leaves.Diabetes was persuaded in albino rats by injecting of alloxan monohydrate .The methanol extract of Nymphaea pubescens leaves at a dose of 250mg/kg and 500mg/kg body weight were administered at single dose per day to diabetes induced rats for a period of 28 days. The effect of methanol extract of Nymphaea pubescens leaves extract on blood glucose(48), glycosylated haemoglobin (HbA1C) (3), Alanine aminotransferase (ALT) (38.5) and Aspartate aminotransferase (AST) (56) level. serum lipid profile total cholesterol (TC) (56.5), triglyceride (TG) (44), low density lipoprotein- cholesterol (LDL-C) (10.5), high density lipoprotein- cholesterol (HDL-C) (39) and catalase (CAT) (0.51), lipoprotein peroxidation (LPO) (0.134), blood reduced glutathione (GSH) (0.169) were measured in the diabetic rats. The methanol extracts of Nymphaea pubescens leaves elicited significant (p<0.05) Declines of blood glucose, lipid parameters except HDL-Cholestrol,serum enzymes and significantly increased HDL-C and antioxidant. In conclusion, the methanol extract of Nymphaea pubescens leaves offers promising antidiabetic and hypolipidaemic effects compared with control drug that may be mainly attributed to its potent antioxidant potential. Additional research will be needed in future in order to conclude which one of its active components have the main antidiabetic and hypolidaemic effects.